2003
DOI: 10.1038/sj.cgt.7700555
|View full text |Cite
|
Sign up to set email alerts
|

Radiation increases the activity of oncolytic adenovirus cancer gene therapy vectors that overexpress the ADP (E3-11.6K) protein

Abstract: We have described three potential adenovirus type 5 (Ad5)-based replication-competent cancer gene therapy vectors named KD1, KD3, and VRX-007. All three vectors overexpress an Ad5 protein named Adenovirus Death Protein (ADP, also named E3-11.6 K protein). ADP is required for efficient lysis of Ad5-infected cells and spread of virus from cell to cell, and thus its overexpression increases the oncolytic activity of the vectors. KD1 and KD3 contain mutations in the Ad5 E1A gene that knock out binding of the E1A p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 30 publications
2
29
0
Order By: Relevance
“…Studies by others on the effects of irradiation on adenovirus replication in vitro have yielded conflicting results. Increases in viral burst size of the prostate cell -specific oncolytic adenoviruses CV706 and CG7870 in combination with irradiation have been reported (12,15), as well as decreases in viral DNA synthesis in irradiated cells infected with ADP-overexpressing oncolytic adenoviruses (26). For the E1-B -deleted oncolytic adenovirus dl1520 (ONYX-015), no significant effect of irradiation on virus replication was found (27), consistent with our results.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Studies by others on the effects of irradiation on adenovirus replication in vitro have yielded conflicting results. Increases in viral burst size of the prostate cell -specific oncolytic adenoviruses CV706 and CG7870 in combination with irradiation have been reported (12,15), as well as decreases in viral DNA synthesis in irradiated cells infected with ADP-overexpressing oncolytic adenoviruses (26). For the E1-B -deleted oncolytic adenovirus dl1520 (ONYX-015), no significant effect of irradiation on virus replication was found (27), consistent with our results.…”
Section: Discussionsupporting
confidence: 90%
“…This more general mechanism of enhanced antitumor efficacy of oncolytic adenoviruses in combination with radiotherapy is presumed to be operative in s.c. tumor models as well. Indeed, we and others have shown the potentiating effect of irradiation on the antitumor activity of various oncolytic adenoviruses in a variety of s.c. xenografts (10,12,13,15,26,27). Again, both increases (12) and decreases (13) in intratumoral adenovirus replication in irradiated tumors were reported.…”
Section: Discussionmentioning
confidence: 99%
“…However, docetaxel in combination with Xvir03 causes increased growth delay of DU145 xenograft compared with treatment with either docetaxel or virus alone. Considering the fact that Xvir03 does not express the adenoviral death protein (50) and E1A proteins suggests that it should be possible to design adenoviral mutants that are even more effective in achieving enhanced antitumor effects in combination with chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Malignant tumors that express adenoviral proteins may become more sensitive to treatment with DNA-damaging agents such as radiation in vivo. Toth et al 20 have recently reported that the combination of radiation plus oncolytic adenovirus suppresses the growth of A549 lung adenocarcinoma xenografts in nude mice more efficiently than either radiation alone or oncolytic vector alone. Our current findings with CG7870 clearly show that the virotherapy and radiation combination significantly improves both cytotoxicity and virus burst size in vitro as well as efficacy in the xenograft tumor model in vivo, but without a concomitant increase in toxicity.…”
Section: Discussionmentioning
confidence: 99%